POSTĘPOWANIE WEWNĄTRZSPÓŁDZIELCZE I ZASKARŻANIE UCHWAŁ WALNEGO ZGROMADZENIA W ŚWIETLE ZASADY SAMORZĄDNOŚCI SPÓŁDZIELNI - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 2006)
Since 1920 until very recently Polish law on co-operatives had provided for disputes between a co-operative and its member to be first recognised and settled in the proceedings within the co-operative itself, i.e. in internal proceedings, and only the exhaustion of those opened the way to court proceedings. This concerned mainly disputes arising from the status of the membership (such as striking off the list of members). The amendments of the Law on Co-operatives of 2005 deprived internal proceedings in a co-operative of a statutory status, and nowadays they may only be resorted to in co-operatives whose articles of association provide for such a regulation. This change is an overt attempt to limit the autonomy of a co-operative and allow wider interference in co-operative matters of external bodies. Needless to say, although the internal proceedings had never precluded the right of a member to file a complaint with a court, they were often used to avoid the costly and lengthy court proceedings, and most of the decisions settling disputes so reached had been satisfactory. The authors of the amendments implemented in 2005 had abandoned the principle that had been in force since 1920, restricting the grounds for challenging shareholders' resolutions in court proceedings to: (i) the conflict with the existing laws or (ii) the conflict with the articles of association. The amended laws provide for such, sometimes enigmatic, grounds of challenging shareholders' resolutions as: good practice, conflict with the co-operative interests, or intentional harm to a member. However, the doctrine, the judicial decisions, and the co-operative practice so far have not offered any serious arguments to justify such widening of the list of grounds for the challenging of the resolutions of the highest organ of a co-operative. In practice, this may entangle co-operatives in numerous disputes in court, which, at best, will impede smooth management of a co-operative will does not serve the best interest of its members (articles 1 and 67 of the Law on Co-operatives).
INTERNAL PROCEEDINGS AND THE CHALLENGING OF SHAREHOLDERS’ RESOLUTIONS IN THE LIGHT OF THE CO-OPERATIVE AUTONOMY PRINCIPLE